#### Answer

solution

#### Work Step by Step

Plug in -4 for x and simplify to see if the equation is true or false.
2(x+3)-18=5x
2(-4+3)-18=5(-4)
2(-4)+2(3)-18=-20
-8+6-18=-20
-2-18=-20
-20=-20
This is a solution.

Published by
Pearson

ISBN 10:
0-13417-805-X

ISBN 13:
978-0-13417-805-9

solution

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.